Automated radiosynthesis of [11C]L-deprenyl-D2 and [11C]D-deprenyl using a commercial platform. (April 2016) - Buccino, Pablo; Kreimerman, Ingrid; Zirbesegger, Kevin; Porcal, Williams; Savio, Eduardo; Engler, Henry
Abstract: Two 11 C-labelled PET tracers, ( R )- N -[ 11 C]methyl- N -(3, 3-dideuteropropargyl)-1-phenylpropan-2-amine ([ 11 C]L-deprenyl-D2, [ 11 C]DED) and ( S )- N -[ 11 C]methyl- N -propargyl-1-phenylpropan-2-amine ([ 11 C]D-deprenyl, [ 11 C]DDE) were synthesised. One step N -alkylation with [ 11 C]MeI or [ 11 C]MeOTf was performed using the automated platform TRACERlab® FX-C Pro. The labelled products were obtained with (37±15)% ( n =10) (end of synthesis, decay corrected from [ 11 C]MeI) radiochemical yields from [ 11 C]MeI after 38±3 min synthesis time. In all cases, radiochemical purity was over 99% when [ 11 C]MeOTf was used. This synthesis using a commercial platform makes these tracers more accessible for clinical research purposes. Highlights: Two 11 C PET tracers, [ 11 C]L-deprenyl-D2 and [ 11 C]D-deprenyl, were synthesised. Labelling conditions were tested: methylating agent, reaction temperature, solvent and base. Radiotracers were synthesised in a commercial platform using [ 11 C]MeOTf. A facile organic synthesis of [ 11 C]D-deprenyl precursor was developed.